Contribuições em escalonamento e análise de desempenho de redes WirelessHART - Nobre, Marcelo Henrique Ramalho (2015)
Wireless Communication is a trend in the industrial environment nowadays and on this trend, we can highlight the WirelessHART technology. In this situation, it is natural the search for new improvements in the technology and such improvements can be related directly to the routing and scheduling algorithms. In the present thesis, we present a literature review about the main specific solutions for Routing and scheduling for WirelessHART. The thesis also proposes a new scheduling algorithm called Flow Scheduling that intends to improve superframe utilization and flexibility aspects. For validation purposes, we develop a simulation module for the Network Simulator 3 (NS-3) that models aspects like positioning, signal attenuation and energy consumption and provides an link individual error configuration. The module also allows the creation of the scheduling superframe using the Flow and Han Algorithms. In order to validate the new algorithms, we execute a series of comparative tests and evaluate the algorithms performance for link allocation, delay and superframe occupation. In order to validate the physical layer of the simulation module, we statically configure the routing and scheduling aspects and perform reliability and energy consumption tests using various literature topologies and error probabilities.